An Analysis of Psychological Aspect of the Main Character in Cruella Movie - Komang, Aryanti; I. B. Gde Nova Winarta; I Dewa Ayu Devi Maharani Santika (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
This research entitled An Analysis of Psychological Aspect of The Main Character in Cruella Movie aims to analyze behavior and identify the psychological aspects of the main character in Cruella Movie. The data was taken from the Cruella movie which are from scenes and dialogues that containing the Psychological Aspects of Human Motivation. The data were analyzed using the theory proposed by Benhardt (1953) to identify the Psychological Aspects of Human Motivation. In this study, the data were collected using the observation method. The data were observed using note-taking techniques to identify and analyze the data. Data were analyzed using qualitative methods and presented descriptively. The results of this study obtained 24 data relating to the Psychological Aspects of Human Motivation experienced by the main character.